An integrated biomarker approach (2022)
Environmental risk assessment in aquatic ecosystems typically uses biomarkers to detect interactions between potential hazards and biological systems. Next to knowing environmental contaminant levels in tissues and the environment, it is important to link to potentially deleterious effects at higher levels of biological organization such as biochemistry, physiology, and overall health status. In this laboratory study we assessed the toxicity of waterborne cadmium (Cd) over an exposure range of 0 - 100 µg l−1 for nine days to the loricariid suckermouth catfish Hypostomus plecostomus. We evaluated the integrated response of the fish at the biochemical to physiological level by means of a suite of tissue biomarkers of exposure and effects, including Cd concentrations in gills, liver metallothioneins (MT) and cholinesterase activity (ChE) in brain, before and after the inhibition of the alkaloid eserine, as well as whole-fish resting oxygen consumption rates and ingestion rate. Tissue biomarkers (MT and ChE) showed a non-monotonic relationship, with maximum/minimum responses at intermediate doses. i.e. 10 and 50 µg l−1, whereas biomarker responses of fish exposed at 100 µg l−1 more closely resembled biomarker responses seen at lower concentrations (< 10 µg l−1). Conversely, the oxygen consumption rate peaked at 100 µg l−1, suggesting a higher metabolic cost for higher metal exposure, with no significant correlation with fish body condition and food intake. Integrated Biomarker Response (IBR) values peaked at the intermediate exposure concentration of 50 µg l−1 Cd. The non-monotonic dose-response of the biochemical biomarkers of exposure, together with the higher metabolic rates of fish exposed to 50 - 100 µg l−1 of Cd and the non-significant effects on the more relevant physiological and histological variables suggests that H. plecostomus is capable of biochemically and physiologically regulating moderately high Cd concentrations, thus representing a suitable indicator organism to monitor metal pollution by Cd.